What You Need to Apply for Disaster Rehabilitation Assistance: DH206/DH206, rev. 10/2019 - Fountain, Carol; Olexa, Michael T.; Caracciolo, Jana; Grant, Lauren (EDIS, 2019)
After a disaster, you may need to seek financial assistance to restore your home or farm. There are many sources of assistance, but you will be required to provide certain information. The lists in this publication can help you assemble the necessary information before you meet with any agents. This 1-page fact sheet is a minor revision written by Michael T. Olexa, Jana Caracciolo, and Lauren Grant, and published by the Food and Resource Economics Department, October 2019. DH206/DH206: What You Need to Apply for Disaster Rehabilitation Assistance (ufl.edu)